The Effecf of Using a Differentiated Second-graders, Intermediate, in Social Studies and the Development of Their Inferential Thinking - Al- Samarrai, Murad Ahmed Khalaf; Qadir Al-Alawi, Aous Memir (Journal of Tikrit University for Humanities, 2020)
The aim of the current research is to identify the role of using differentiated education strategy in the results of the second intermediate grade students in geographic article and development of inferential thinking. For this purpose, we chose three Zero hypotheses, the Randomly check from Al-Zahrawi secondary school for boys, affiliated to the General Directorate of Education, Salah Al-Din – Samarra breeding section . Experimental design was used from two equal groups ( Experimental group and control group) based on the achievement test – two clauses were chosen randomly to sample of 64 students. The first experimental group was conducted according to the differentiated education strategy had 32 students. The control groups that studied according to the usual method has 32 student too. the two researchers were equaled between the two groups in the changes of age –previous academic achievement in the social studies subject for the first intermediate grade – intelligence lest and inferential reasoning test. The research supplies prepared by the two researchers. Such as determine the scientific subject – from – calculation of behavioral purposes – preparing the teaching plans. The two researchers made a final test of forty questions ( multiple choice exam ), the apparent honesty was verified and the difficulty discrimination and efficacy factor of the alternative were extracted and a fixed test paragraphs were found to use the alpha – croping equation which reached to ( 0.82 ) in the inferential thinking test the two researchers choose ( Alqubase and Abdallah test 2015 which has 28 questions and after checking its truth and identification of questions and consistency in a alpha – cropang method which reached to ( 0.79 ). The experiment was applied in the first semester and lasted into weeks. After the experiment was completed, the research tools were applied to the two research groups to measure achievement and inferential thinking . The data were statistically processed . the results of the research showed the superiority of the experimental group that was studied according to the differentiated education strategy over the control group that studied in the usual way. A ccording to the results of the research. A set of conclusions were reached a set of recommendations and proposal were presented